Revealing the Power of Minds Online: Validating Instruments for Reflective Thinking, Self-Efficacy, and Self-Regulated Learning - Sapriati Amalia; Sekarwinahyu Mestika; Puspitasari Maya; Amastini Fitria (Open Education Studies)
This study presents a new instrument for assessing reflective thinking, self-efficacy, and self-regulated learning (SRL) among Universitas Terbuka postgraduate students registered in an online Research Methods course. The study validates the instrument’s dependability (Cronbach’s alpha = 0.918) and builds a strong factor structure by means of statistical techniques including factor analysis and partial least squares structural equation modeling, therefore addressing 56% of the variance. Strong interrelationships between reflective thinking, self-efficacy, and SRL are revealed by the study, therefore underscoring their joint functions in improving online learning environments. Although the results highlight the need for these abilities in promoting academic performance in higher education, the study warns against generalizing results considering the particular demographic of the participants. It demands more study conducted in several learning environments. This article might provide useful insights for teachers and researchers looking to develop these important crucial abilities in online learning environments. It may then lead to enhance student results and results in more efficient decision-making in remote education contexts.